Wireless sensor networks leveraging the virtual infrastructure. - Olariu, S.
Overlaying a virtual infrastructure over a physical network is a time-honored strategy for conquering scale. We design a general-purpose virtual architecture for wireless sensor networks and show that it can be leveraged by a number of different protocols.
Keywords: General-purpose virtual architecture; Physical network; Protocols; Virtual infrastructure; Wireless sensor networks